How do you solve #2(f-3) + 5 = 3(f-1)#?

1 Answer
Jun 17, 2018

Answer:

#color(blue)(f=2)#

Explanation:

Given
#color(white)("XXX")2(f-3)+5=3(f-1)#

Simplifying each side:
#L.S.#
#color(white)("XXX")=2(f-3)+5#
#color(white)("XXX")=2f-6+5#
#color(white)("XXX")=2f-1#
#R.S.#
#color(white)("XXX")=3(f-1)#
#color(white)("XXX")=3f-3#

Since #L.S.=R.S.#
#color(white)("XXX")2f-1=3f-3#

Subtracting #2f# from both sides
#color(white)("XXX")-1=f-3#
then adding #3# to both sides
#color(white)("XXX")2=fcolor(white)("xxxxxxxx")" or, if you prefer: "f=2#